Survey of Physical Fitness Levels in Educational Park Using Outdoor Laboratory - Rian, Muhamad; Hartati, Hartati; Destriana, Destriana (Universitas Negeri Semarang, 2023)
The objective of the survey on the physical fitness level of class VII students at SMP Negeri 2 Indralaya Utara utilizing an outdoor laboratory in an educational park is to present the findings. This study's methodology employs a survey approach. The Indonesian Physical Fitness Test (TKJI) norm test instrument was utilized to gather the descriptive outcome data for this investigation. Seventy students from class VII at SMP Negeri 2 Indralaya Utara served as the study subjects. Purposive sampling was utilized to choose the participants, and test measurement procedures were used to evaluate the results. The physical fitness levels of class VII students at SMP Negeri 2 Indralaya Utara were used to provide quantitative descriptive data, with 79% of the pupils falling into the moderate classification, 14% into the good classification, and 7 % into the less classification. The result of this study shows an increasing awareness among SMP Negeri 2 Indralaya Utara students on the importance of maintaining their physical health. According to the TKJI norm table, the study's findings indicate that SMP Negeri 2 Indralaya Utara pupils likely to have physical fitness levels that fall into the moderate group (S).